USE OF LINGUISTIC AND CULTURAL APPROACH IN TEACHING MODERN GREEK AT SECONDARY SCHOOLS OF UKRAINE - Катерина Колесник (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2014)
The mother tongue of the Greeks of Ukraine is Modern Greek, since Rumaiic and Urum dialects are not introduced into the education system. To eliminate this situation, it is recommended to apply the integrated study of language and culture. Learning Modern Greek on the basis of linguistic and cultural approach presupposes teaching students to perceive the language not as a purely grammatical scheme, but as a phenomenon of philosophy, history and culture of Greece and the Greeks of Ukraine.